2013
DOI: 10.1080/1357650x.2012.746349
|View full text |Cite
|
Sign up to set email alerts
|

Lateral bias in theatre-seat choice

Abstract: Examples of behavioural asymmetries are common in the range of human behaviour; even when faced with a symmetrical environment people demonstrate reliable asymmetries in behaviours like gesturing, cradling, and even seating. One such asymmetry is the observation that participants tend to choose seats to the right of the screen when asked to select their preferred seating location in a movie theatre. However, these results are based on seat selection using a seating chart rather than examining real seat choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…A second study found the same results using a similar procedure (Weyers, Milnik, Muller, & Pauli, 2006). The findings of both these studies have been replicated in a very recent study which investigated the real-world seating patterns of theatre patrons during actual film screenings and reported a significant bias to choose seats on the right side of the theatre (Harms, Reese, & Elias, 2014). …”
Section: Directionality Bias In Turning or Rotational Behaviormentioning
confidence: 66%
“…A second study found the same results using a similar procedure (Weyers, Milnik, Muller, & Pauli, 2006). The findings of both these studies have been replicated in a very recent study which investigated the real-world seating patterns of theatre patrons during actual film screenings and reported a significant bias to choose seats on the right side of the theatre (Harms, Reese, & Elias, 2014). …”
Section: Directionality Bias In Turning or Rotational Behaviormentioning
confidence: 66%
“…Such asymmetries with a bias towards the right side were shown on a number of behaviors, including the higher probability of turning to the right when kissing (Barrett, Greenwood, & McCullagh, 2006), the tendency to turn right in a T-maze (Scharine and McBeath, 2002), and others. An example of the lateral bias that is most relevant to our case, because it also depicts bias in choice from the display, is a tendency to choose theatre seats from the right side of the seating chart (Karev, 2000), which was confirmed by actual seating behavior (Harms, Reese, and Elias, 2014). We consider the possibility of the lateral bias interpretation due to the fact that green-yellow, red, violet, and blue-violet spectra that represent hue biases across all stimuli were situated on the right side of the HSV color wheel used in the study.…”
Section: Discussionmentioning
confidence: 93%
“…Turning behaviors of individuals entering a symmetrical theatre are found to depend on the purpose and motivation of the presentation. When examining real-world seating biases of movie-goers, individuals display a right-side bias (Harms et al 2014); however, when participants are told they are negatively motivated to view the film, the right-directional bias disappears (Okubo 2010). Lateral head-turning in picture posing similarly differs by the context in which it is framed.…”
Section: Discussionmentioning
confidence: 98%